Effect of cold atmospheric plasma jet associated to polyene antifungals on Candida albicans biofilms - Koga-Ito, Cristiane Yumi [UNESP] (2021)
: The increasing incidence of antifungal resistance represents a great challenge in the medical area and, for this reason, new therapeutic alternatives for the treatment of fungal infections are urgently required. Cold atmospheric plasma (CAP) has been proposed as a promising alternative technique for the treatment of superficial candidiasis, with inhibitory effect both in vitro and in vivo. However, little is known on the association of CAP with conventional antifungals. The aim of this study was to evaluate the effects of the association between CAP and conventional polyene antifungals on Candida albicans biofilms. C. albicans SC 5314 and a clinical isolate were used to grow 24 or 48 h biofilms, under standardized conditions. After that, the biofilms were exposed to nystatin, amphotericin B and CAP, separately or in combination. Different concentrations of the antifungals and sequences of treatment were evaluated to establish the most effective protocol. Biofilms viability after the treatments was compared to negative control. Data were compared by One-way ANOVA and post hoc Tukey (5%). The results demonstrate that 5 min exposure to CAP showed more effective antifungal effect on biofilms when compared to nystatin and amphotericin B. Additionally, it was detected that CAP showed similar (but smaller in magnitude) effects when applied in association with nystatin and amphotericin B at 40 µg/mL and 60 µg/mL. Therefore, it can be concluded that the application of CAP alone was more effective against C. albicans biofilms than in combination with conventional polyene antifungal agents.